2018
DOI: 10.1093/jac/dky074
|View full text |Cite
|
Sign up to set email alerts
|

Relentless spread and adaptation of non-typeable vanA vancomycin-resistant Enterococcus faecium: a genome-wide investigation

Abstract: These findings confirmed the evolution, emergence and dissemination of non-typeable vanA E. faecium. This study has highlighted the utility of WGS when attempting to describe accurately the hospital-based pathogen epidemiology, which in turn will continue to inform optimal infection control measures necessary to halt the spread of this important nosocomial organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…Most of the Australian pstS -null genomes we analysed were ST1421 (Fig. 1C), in agreement with recent data showing that ST1421 is the most common and widespread pstS -null VRE strain in Australia, accounting for more than 70% of the cases [25,26]. Since both Australian [8] and Scottish (this study) VREfm pstS -null strains were found in different hospitals (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Most of the Australian pstS -null genomes we analysed were ST1421 (Fig. 1C), in agreement with recent data showing that ST1421 is the most common and widespread pstS -null VRE strain in Australia, accounting for more than 70% of the cases [25,26]. Since both Australian [8] and Scottish (this study) VREfm pstS -null strains were found in different hospitals (Fig.…”
Section: Resultssupporting
confidence: 91%
“…We then performed a phylogenetic comparison of VREF001-5 genomes with other known VREfm genomes reported to have a missing pstS locus; these included: 14 (out of 66 reported) Australian strains isolated from 9 different hospitals between 2014 and 2015 [8], 5 Australian strains (out of 202 reported within 6 local health districts) isolated from 2 different local health districts (LHD-1 and LHD-2) in New South Wales during 2016 [25], and all 5 English pstS -null E. faecium strains isolated from a single hospital (Kathy Raven, personal communication) in 2005 [7]. In our phylogenetic analysis we also included: 5 hospital-associated isolates of different MLST sequence type each, 3 isolates (BM4538, UAA1025 and E2883) previously reported to have an insertion in the tetM -locus [16] and the first complete E. faecium genome, Aus0004 [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Australia, as in Europe, the major pathogen surveillance programs such as Australian Group for Antimicrobial Resistance (AGAR) and the Victorian Hospital Pathogens Surveillance System (VHPSS) [11, 12] focus on isolates from bacteremic patients, meaning the true burden of MDROs, many of which lead to colonization or non-bacteremic infection, is undefined and poorly understood [9, 11]. Australia has one the highest rates of VRE in the world (47.0% in 2017 [13]), having been dominated by vanB until the last five years, when vanA VRE has emerged rapidly across multiple states [14]. Whilst the patient risk factors of MDRO acquisition are well understood for most of these organisms [15-22], further analysis using whole genome sequencing has the potential to add further insights, particularly defining the relatedness of isolates by genomics (and hence putative transmission when combined with epidemiologic data), which to date has only just started to be applied in a clinical setting [23, 24].…”
Section: Introductionmentioning
confidence: 99%